AN ECONOMIC IMPACT OF COVID-19 ON SME SECTOR IN SRI LANKA - K.G.N.W.Abeyrathna; D.G.A. Chamara (Scholar Express Journals, 2021)
Covid- 19 is a health hazard and crisis which has been affecting human immune system badly. This pandemic became a social and economic threat to every society throughout the world. Due to the lockdown and temporary travel restrictions imposed, businesses had to face a serious decline and as a result of this impact made on small and medium enterprises, they too had to face several problems such as short term and loan term financing, employment declining, bank loan facility problems and other financial and non-financial issues which finally led to the closure or slow growth of their businesses. To explore the above reasons, still a comprehensive a study has not been done in Sri Lanka and in other countries due to the ongoing pandemic. This study was conducted to explore the causes and consequences for the issues faced by SMEs in Sri Lanka and the rest of the world. This study represents fifty Small and Medium Retail shops, printing and photocopy shops and tuition providers in the Gangodawila, Nugegoda, in Sri Lanka and this research used the purposive sampling technique. The research also used the Google documents for the data collection due to the travel restrictions and health reasons. This study will hopefully contribute to the factor for support, rehabilitation and to sort out the problems of the businesses as well as to contribute to the policy. measures of the government.
Keywords: Small and Medium Enterprises; Covid-19; Business; Health